Tillage depth influence on soil nitrogen distribution and availability in a rice lowland - Kundu, D.K.; Ladha, J.K.; Lapitan-de Guzman, E. (Wiley, 1996)
Previous studies using artificial barriers at selected depths have shown the importance of N supply from soil below 15 cm to rice (Oryza sativa L.). Subsoil N availability and its use by wetland rice, however, have not been evaluated under normal field conditions. We examined distribution and availability of 2 M KCl‐extractable N in 0‐ to 15‐, 15‐ to 30‐, and 30‐ to 45‐cm layers of a submerged Alfisol during three successive crop seasons, as influenced by the depth of tillage imposed at the outset of the experiment. Mineral N availability in the 0‐ to 45‐cm profile and rice N uptake in the first season were significantly higher (20–25 kg ha−1 higher mineral N and 16–18 kg ha−1 higher crop N uptake) with tillage to a depth of 40 cm than to 15 or 25 cm, the increased N supply originating largely from the 15‐ to 30‐cm layer. In two following seasons, tillage to 40 cm gave the highest mineral N in the subsoil layers, and increased rice N uptake by 12 to 14 kg ha−1, compared with tillage to 15 cm. The beneficial effects of deep tillage were attributed to the elimination of mechanical impedence to root proliferation, and lower susceptibility of subsoil N to various loss mechanisms. Initial and final analyses of Kjeldahl N in the soil profile indicated no adverse effect of practicing 40‐cm‐deep tillage once in three seasons on soil N fertility. Further study is needed to determine optimum depth and frequency of primary tillage for different soil types to enhance N use efficiency.